Transformasi Pembelajaran PKn Berbasis Inovasi dalam Pembentukan Karakter Peserta Didik Sekolah Dasar melalui Kurikulum Pembelajaran Mendalam - Arina Wulandari (FKIP UNSULTRA, 2025)
The shift in the educational paradigm towards a Deep Learning Curriculum requires a reconstruction of Civics (PKn) learning in elementary schools to be more meaningful, contextual, and oriented towards building student character. PKn is no longer understood as a normative subject based on memorization, but as a reflective learning vehicle that develops critical understanding, active participation, and emotional involvement of students in civic values. This literature study aims to analyze the form of innovation-based transformation of PKn learning according to the principles of deep learning in order to strengthen student character. The research method uses a Systematic Literature Review (SLR) of books, scientific articles, and research results from 2019–2025. The results indicate that the application of Problem-Based Learning, Project-Based Learning, Citizenship Deep Inquiry, Digital Citizenship Learning, and social simulation-based learning can enhance empathy, social problem-solving skills, digital literacy, critical attitudes, and students' ability to reflect on Pancasila values in real life. Furthermore, the integration of innovative media such as digital comics, interactive videos, deliberation simulation platforms, and augmented reality strengthens the internalization of character values through authentic and meaningful learning experiences. Practically, these findings suggest that elementary school teachers can implement active, technology-supported, and project-based strategies to foster civic competence, moral reasoning, and digital citizenship among students. Schools are encouraged to provide professional development for teachers in deep learning pedagogy and digital integration, as well as adopt authentic assessment tools to monitor and support character formation effectively. Thus, the implementation of an in-depth learning curriculum in Civics supports the development of Pancasila students with character, humanity, and responsibility as citizens.